ISOLASI DAN IDENTIFIKASI SENYAWA TERPENOID YANG AKTIF ANTIBAKTERI PADA HERBA MENIRAN (Phyllanthus niruri Linn) - I W. G. Gunawan; I G. A. Gede Bawa; N. L. Sutrisnayanti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
Isolation and identification of terpenoid, antibacterial compounds meniran herb (Phyllanthus niruri Linn) by GasChromatography – Mass Spectroscophy were carried out. Two kinds of extraction, i.e. maseration using methanoland the sochlet using n-hexane were employed.The extract obtained were contains terpenoids basedon fitochemical test of Liberman-Burchard n-hexaneextract was tested for antimicrobial activity against Escherichia coli ATCC® 25292 and Staphylococcus aureusATCC® 25293. In this study we obtained that n-hexane extract by sochlet extraction showed greater activitycompared to the extract by maseration with methanol, as indiated by disc diameter of inhibition zone. Diametricinhibition zone for these two extract are 1 mm for Escherichia coli and 0,5 mm for Staphylococcus aureus, formethanol extract, and where are 10 mm for Escherichia coli and 12 mm for Staphylococcus aureus for n-hexaneextract.The n-hexane extract was then purified using column chromatography. The pure extract was analyzed usingGas Chromatography - Mass Spectroscophy. Gas Chromatography - Mass Spectroscophy data indicated that theextract contains two compounds, i.e. phytadiene [ M+ ] 278 and 1,2 seco – cladiellan m/z 335 [ M+ - H ].